Domestication and Feed Restriction Programming Organ Index, Dopamine, and Hippocampal Transcriptome Profile in Chickens - Chen, Siyu; Yan, Chao; Xiao, Jinlong; Liu, Wen; Li, Zhiwei; Liu, Hao; Liu, Jian; Zhang, Xiben; Ou, Maojun; Chen, Zelin; Li, Weibo; Zhao, Xingbo (Frontiers in Veterinary Science, 2021)
Domestication process exerts different phenotypic plasticity between slow- and fast-growing breeds of chickens. Feed restriction has a critical role in production performance, physiological plasticity, and stress response. Our study aimed to explore how feed restriction programed the organ index, dopamine, and hippocampal transcriptome profile between slow- and fast-growing chickens, which were fed either ad libitum (SA and FA) or feed restricted 70% of ad libitum (SR and FR) for 30 days. Results showed that feed restriction influenced the brain organ index (P < 0.05), but not the organ index of the heart, liver, and spleen. The slow-growing breed had a higher brain organ index than the fast-growing breed (P < 0.05). Under feed restriction conditions, both the slow- and fast-growing breeds had significantly elevated dopamine concentration (P < 0.05) than those fed ad libitum. In the GO term, up-regulated genes of the FA group were enriched in the mitochondria, respiratory chain, and energy metabolism than the SA group (P < 0.05). Membrane and ribosome were enriched in the cellular component between SR and FR groups (P < 0.05). In the KEGG functional pathways, up-regulated DEGs in the FR group were enriched in the cardiovascular diseases category and neurodegenerative diseases category compared to the FA group (P < 0.05). Down-regulated DEGs in the FA group were enriched in the oxidative phosphorylation, neurodegenerative diseases category (Parkinson’s disease and Huntington’s disease) than the SA group (P < 0.05). Up-regulated DEGs in the FR group were enriched in the cardiovascular disease category, neurodegenerative diseases, and energy metabolism than the SR group (P < 0.05). In conclusion, feed restriction had profound effects on the brain organ index and plasma dopamine in the slow- and fast-growing chickens. Feed restriction may result in the issues of cardiovascular diseases, and neurodegenerative diseases category in the fast-growing breed, but not in the slow-growing breed.